Interactive E-Module Based on WordPress Content Management System to Improve Student Learning Outcomes on Chemical Bond Material: Pengembangan E-Modul Interaktif Berbasis Content Management System (CMS) WordPress untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Ikatan Kimia - Nur Lailatul Fitriyah Abidin; Laura Alden Litha Miranda Irawan; Karina Rike Pratiwi; Revani Putri Iswaji; Dwiningsih, Kusumawati (Universitas Negeri Surabaya, 2025)
This study aims to create a learning media in the form of an interactive e-module based on CMS Wordpress to improve student learning outcomes in chemistry lessons, especially on chemical bonding material. This research uses the type of R&D research. The model used in this research is the 4D model by applying three stages. The subjects of this research are students of SMAN 16 Surabaya. The results of the validation of the product showed that the data on the aspects of content and construct validation were very valid at 90% and 91.6%. This E-Module also obtained a practicality percentage of 88% with a very practical category. Then in terms of effectiveness, based on the increase in pretest-posttest results, the n-gain score is 0.71 which is in the high category. Based on these results, the interactive e-module produced is feasible to use as a learning media to improve participants' learning outcomes.